The many roles of mellitic acid during barium sulfate crystallization - Boon, M.; Freeman, S.; Ogden, Mark; Oliveira, A.; Richmond, W.; Skelton, B.; Jones, Franca (Royal Society of Chemistry, 2015)
The various roles of mellitic acid during barium sulfate crystallization from nucleation to mesocrystal formation are explored and elucidated.